Hormonal profile in rutting and non-rutting periods in dromedary camel (Camelus dromedarius) - Mohamed FARH; Islah LEKTIB; Rita BARGAÂ; Najia EL ABBADI; Fouad RIAD; El Hassane TAHRI; Abdallah SAFWATE; Mohammed EL KHASMI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2018)
The dromedary camel is a seasonally breeding animal. The breeding season (also called “rutting period” or “rut”) of this species coincides with the winter months and is characterized by significant changes in circulating hormonal levels. During the rutting period (winter season), the circulating levels of testosterone, cortisol and thyroid hormones are significantly higher than in the summer (non rutting season), however levels of vitamin D are very low in the winter, compared with those analyzed in non-rutting period (summer season). These changes may modulate the reproduction function and the thermoregulatory adaptation. Concentrations of circulating hormones during the rutting period vary greatly in the literature which could be explained by environmental and experimental conditions. In the camel, understanding the seasonal fluctuations of the hormonal profile of the camels, can contribute to a fundamental knowledge of the reproduction physiology of this species, and will be of great importance to veterinarians in confirming their clinical diagnosis and enhancing the capacities of camel production and reproduction. The mechanisms of TH, glucocorticoids and vitamin D in the modulation of reproductive function and fertility in the dromedary remain to be studied.